Simultaneous vs Staged Procedures for Bilateral Total Knee Arthroplasty: Reduced Infection, Cost, and Readmission Rates Associated With Simultaneous Procedures - Aaron Singh, BA; Travis M. Kotzur, BS; Kathleen Lundquist, MD; Blaire C. Peterson, BS; William H. Young, MD; Chance C. Moore, MD; Frank Buttacavoli, MD (Arthroplasty Today)
Background: Many patients require total knee arthroplasty (TKA) bilaterally; however, there is limited data on bilateral procedures. This study aims to compare medical and surgical complications and hospital-related outcomes between simultaneous and staged bilateral TKA. We hypothesize that staged procedures will have superior outcomes. Methods: This retrospective cohort study queried the National Readmissions Database, years 2016-2020, for patients undergoing bilateral TKA via ICD-10 codes. For patients undergoing staged procedures, outcomes were compared in aggregate for comparison to simultaneous operations. Multivariate regression was performed to assess complications. Negative binomial regression was utilized for 30-day readmission, reoperation, and discharge disposition. Quasi-Poisson regression was performed to assess total charges. Demographics and comorbidities, measured via Elixhauser Comorbidity Index, were controlled for in our analysis. Results: A total of 210,682 patients, 89,568 (42.51%) undergoing simultaneous bilateral and 121,115 (57.49%) undergoing staged bilateral TKA, were included. The staged cohort had higher odds of medical complications (odds ratio (OR), 1.14; P < .001), reduced surgical complications (OR, 0.51; P < .001), and increased odds of routine discharges (OR, 1.39; P < .001). They also had increased odds of readmission (OR, 1.25; P < .001), reoperation (OR, 1.56; P < .001), and greater total charges (OR, 1.18; P < .001). Conclusions: Our results demonstrate that, for some patients, simultaneous procedures may be a viable option. While staged operations were associated with reduced surgical complications and resulted in better discharge dispositions, they were also associated with greater medical complications, readmissions, reoperations, and total cost. Surgeons should consider individual patient risks and preferences when planning bilateral TKA.